Case report: Identification of a recurrent pathogenic DHDDS mutation in Chinese family with epilepsy, intellectual disability and myoclonus - Dong, Yi; Zhang, Yi; Sheng, Yue; Wang, Fang; Liu, Lv; Fan, Liang-Liang (Frontiers in Genetics, 2023)
Background: Heterozygous mutations in the dehydrodolichol diphosphate synthase (DHDDS) gene are one of the causes generating developmental and epileptic encephalopathies. So far, only eleven mutations in the DHDDS gene have been identified. The mutation spectrum of the DHDDS gene in the Chinese population remains unclear. Methods: In this study, we enrolled a Chinese family with myoclonus and/or epilepsy and intellectual disability. The epilepsy and myoclonic tremor were improved after deep brain stimulation (DBS) of the subthalamic nucleus (STN) treatment. Whole exome sequencing and Sanger sequencing were employed to explore the genetic variations of the family. Results: Subsequent to data filtering, we identified a recurrent pathogenic mutation (NM_001243564.1, c.113G>A/p.R38H) in the DHDDS gene in the proband. Sanger sequencing further validated that the presence of the mutation in his affected mother but absent in the health family members. Further bioinformatics analysis revealed that this mutation (p.R38H), located in an evolutionarily conserved region of DHDDS, was predicted to be deleterious. Discussion: In this report, we present the first case of intractable epilepsy and/or myoclonus caused by p.R38H mutation of the DHDDS gene in the Chinese population. Furthermore, this study represents the third report of autosomal dominant familial inheritance of DHDDS mutation worldwide.